Candidalysin activates innate epithelial immune responses via epidermal growth factor receptor - Jemima Ho (Nature Portfolio, 2019)
Candida albicans is an opportunistic fungus primarily affecting immunocompromised patients. Here, the authors identify a novel mechanism of host immune stimulation and highlight candidalysin and EGFR signalling components as potential targets for prophylactic and therapeutic intervention of mucosal candidiasis.